Performance of macaroni wheat (Triticum durum) under nitrogen and phosphorus and sowing dates - KUMAR, SANJEEV; SINGH, HARBIR; KUMAR, RAJENDER; SINGH, B P (The Indian Journal of Agricultural Sciences, 2013)
In biennial field trials during winter season of 1994-95 and 1995-96 on sandy loam soil at Hisar 6 fertilityvariants (N0'P0 N30 P6.6 N60'P13.2' N90 P19.8' N120 P26.4 and N150 P33) under 3 dates of sowing (1, 15 and 30 November) weretested with 'WH 896' macaroni wheat. Date of sowing influenced the spikes/row, grains/spike, grain weight/spike, 1OOO-grain weight, and finally the grain yield of macaroni wheat. Delayed sowing beyond 15 November reduced thevalues for various yield components and grain yield. Among different fertility levels, though N 150 P33 recorded highestgrain yield and yield components which, however, did not differ from N 120 P26.4 its resulted in significant increase in thevalues of most of the yield attributing characters (spike/m row; grains/spike, grain weight/spike, I OOO-grain weight)and final grain yield of macaroni wheat.